First record of semi-aquatic bugs (Hemiptera: Veliidae) from Tasik Ria coastal waters, North Sulawesi, Indonesia - Warouw, Veibe; Rimper, Joice R.T.S.L; Harikedua, Silvana Dinaintang; Manembu, Indri Shelovita; Rumampuk, Natalie Detty (Universitas Sam Ratulangi, 2025)
Semi-aquatic bugs of the family Veliidae (Hemiptera: Heteroptera: Gerromorpha) are primarily associated with freshwater habitats; their occurrence in coastal environments remains poorly documented, particularly in tropical regions. This study reports the first record of Veliidae from the coastal waters of Tasik Ria Beach, North Sulawesi, Indonesia, thereby expanding the known ecological distribution of this family. Specimens were collected from surface-water microhabitats using a sweep net, and key environmental parameters were measured in situ. Morphological identification was based on stereomicroscopic examination of diagnostic characters. Molecular confirmation was obtained through DNA barcoding of the mitochondrial cytochrome c oxidase subunit I (COI) gene, with sequences compared against the GenBank and BOLD databases. Both morphological and molecular analyses confirmed the specimens' taxonomic placement within Veliidae. Their presence in a coastal habitat indicates greater ecological plasticity and habitat tolerance than previously recognized. This finding establishes important baseline data for future research on the distribution, bioecology, and adaptive strategies of semi-aquatic insects in tropical coastal ecosystems.